2017
DOI: 10.19173/irrodl.v18i5.3014
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Social Media in E-Learning: A Metasynthesis

Abstract: The adoption of social media in e-learning signals the end of distance education as we know it in higher education. However, it appears to have very little impact on the way in which open and distance learning (ODL) institutions are functioning. Earlier research suggests that a significant part of the explanation for the slow uptake of social media in e-learning lies outside of conventional factors attributed to distance learning reforms.This research used the conceptual framework for online collaborative lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 14 publications
0
39
0
Order By: Relevance
“…As social networking and social media technology approach maturity, they have become applicable to learning activities and online learning thereby facilitating learning interactions among teachers and students (Mnkandla & Minnaar, 2017). However, from a learning design perspective, social networking applications specifically designed for learning must be more functional than simply encouraging users to be constantly aware of what their friends do or care about.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As social networking and social media technology approach maturity, they have become applicable to learning activities and online learning thereby facilitating learning interactions among teachers and students (Mnkandla & Minnaar, 2017). However, from a learning design perspective, social networking applications specifically designed for learning must be more functional than simply encouraging users to be constantly aware of what their friends do or care about.…”
Section: Resultsmentioning
confidence: 99%
“…With a deliberate learning activity design, learners can achieve higher learning performance. For example, Mnkandla and Minnaar (2017) found that social media could adopt a conceptual framework for online collaborative learning (OCL) to facilitate deep learning and the creation of knowledge in e-learning at higher educational institutions. Gülbahar et al (2017) also found that providing instructors with a social media toolkit served as a guide to steer the students' discussions in the appropriate direction.…”
Section: Social Networking Enhanced Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the core of logistics of social media supported learning is how to coordinate all the basic operational tasks described above to produce the expected learning outcomes. Besides following the theories or design models, instructors may want to change some traditional thoughts about teaching and learning, as this is really an equal involvement procedures from both the learners and the instructor (Ab Rashid, Yahaya, Rahman, & Yunus, 2016;Mnkandla & Minnaar, 2017). Instructors need to involve in the learning activities with students to obtain the first hand dynamic assessment data, along with the ongoing performance data collected from the information platform, so dynamic learning can constantly move to the right direction, and produce expected learning outcomes (Liu & Chen, 2018).…”
Section: Logistics Of Social Media Supported Learningmentioning
confidence: 99%
“…In an academic context, social media is used in University, teacher education, and school settings because it plays a decisive role in meeting students' needs and accessible on the variety of devices (Ahern, Feller, & Nagle, 2016). For example, Lecturers often use Blogs, Skype, Wikis, Facebook; and even mobile apps, such as WhatsApp in distance learning in University (Mnkandla & Minnaar, 2017;Owusu-Ansah, Gontshi, Mutibwa, & Ukwuoma, 2015;Callaghan & Fribbance, 2016;Hussain, Cakir, & Candeger, 2018). The most common use of social media includes searching and studying in collaborative online activities, download media, sharing information, and entertainment (Wheeler, Yeomans, & Wheeler, 2008;Al-Daihani, Jumanah, & Sara, 2018).…”
Section: Introductionmentioning
confidence: 99%